Implementasi Personal Hygiene pada Orang dengan Gangguan Jiwa - Endah Sari Purbaningsih; Muadi Muadi; Sri Qomalasari; Naufah Fitriyani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Mental health has now become a global health problem for every country, where the process of globalization and the rapid progress of information technology has an impact on the social and cultural values ​​of society. Clients with mental disorders have several problems, including a self-care deficit. The method used was assessment, implementation and evaluation with a sample size of 5 respondents with the inclusion criteria being clients who experienced self-care deficits. The results showed that all 5 respondents experienced self-care deficits, the actions taken were identifying the client's abilities, teaching the client in personal hygiene and helping the client to carry out personal hygiene. The nurse's task is to be able to provide professional nursing actions in order to reduce problems and achieve targets to increase the client's independence in carrying out self-care, marked by the client being able to fulfill personal hygiene needs independently.